KEMAMPUAN MEMBACAKAN BERITA SISWA KELAS XI SMA N 1 PAINAN MENGGUNAKAN MEDIA AUDIO VISUAL - Vembriwazi, Ririt; Nisja, Indriani; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2014)
This research is motivated first, the lack of interest of students to read the news, zecond, students are in able to understand the elements that must be considered in reading the news, third, instructional methods used by teachers are less varied and monotonous. This study aimed to obtain a description of " the ability of a class XI students SMA N 1 Painan in reading the news using audio-visual media in accordance with the elements of reading the news like intonation, pronunciation , and the the performance". This research is a quantitative research using descriptive methods. The results of the study are (1) the ability to read the news seen from intonation obtain an average value of 76.34 is at a good level qualification with 76-85% mastery level, (2) the ability to read news views of pronunciation obtain an average value of 71.03 was the qualifying level is more than adequate to the level of mastery of 66-75%, (3) the ability to read the news seen from the attitude obtain an average value of 75.85 was the qualifying level of more than quite to the level of 66-75% mastery. Based on the research and analysis of the data, we conclud that the ability to read a class XI students news SMA N 1 Painan using audio-visual media obtain an average value of 74.32 was more than enough in qualifying with a mastery level of 66-75% .